PROGRAM FOR THE CESSATION OF SMOKING: PROFILE AND RESULTS - Luppi, Claudia Helena Bronzato (2010)
Introduction: Smoking, regarded as the consumption of tobacco, characterized by acute or chronic intoxication resulting from the habit of smoking and, therefore, in need of treatment. Objective: Characterize smokers attended by the Program for the Cessation of Smoking of the Smoking Ambulatory. Methodology: The population consisted of 159 individuals, attended in 2003 and 2004, with the effective participation of 92 individuals in the program. The collection of data was performed by means of a previously elaborated questionnaire, in addition to the FTND (Fagerstrom Test for Nicotine Dependence). Results: The predominant age group (73%) varied between 31-50 years old. Regarding the participants general characteristics: 57.2% were female, 57.6% were married, 54.1% possessed 1st grade schooling, 50% received 2 to 4 times the minimum wage, 45.6% sought the service voluntarily and 43.3% received medical referral. In relation to health problems, hypertension, gastro pathologies, asthma and pulmonary emphysema were cited by 45.1% of the individuals. Among the respiratory symptoms, 86.1% reported the presence of one or more of the following: coughing, catarrh, wheezing or lack of air. Most of the patients began smoking between the ages of 11–20 (81.1%). Daily consumption was established between 11 to 20 cigarettes (57.9%). With regards to the duration of the habit, 66.7% were found to have 11 to 30 years of consumption, while 74.5% had effected one or more previous attempts to stop smoking. The final results of Fagerstrom’s Test revealed that 39% of the patients scored a high level of dependency (6-7) and 37.7% scored at an extremely high level (8-10). Among the 92 individuals that completed the program, 35.9% obtained a successful outcome through treatment, and in regard to the chosen resource, 30.3% used medication and only 3% opted for nicotine gum. Conclusions: Social condition and level of schooling can influence treatment, in terms of understanding the content and adequate use of resources. The world-wide tendency of increased smoking among women was confirmed. Adolescence was characterized as the predominant age group for the initiation of the habit, reaffirming the concept established in scientific circles. Smokers present larger prevalence values for respiratory symptoms, an expected result in virtue of the condition of smoking and habit duration. Despite the dependency scores, the results of the program presented are satisfactory, probably due to previous experiences of interruption which gradually contributed to the decision for behavioral change and also in function of the adequate use of resources.